2008
DOI: 10.1149/1.2905857
|View full text |Cite
|
Sign up to set email alerts
|

PEM Fuel Cell Operation at −20°C.

Abstract: An experimental procedure using isothermal galvanostatic operation was developed to quantify the charge ͑water͒ accumulation in proton exchange membrane ͑PEM͒ fuel cells at subfreezing conditions prior to voltage failure ͑i.e., zero cell voltage͒. The charge passed until voltage failure was compared to charge ͑water͒ storage estimates in the membrane phase and the cathode electrode void volume. Cryo-scanning electron microscope images of electrodes following voltage failure were used to assess ice filling of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(100 citation statements)
references
References 15 publications
5
95
0
Order By: Relevance
“…These results are consistent with those reported earlier where the initial membrane water content, λ, was 14 mol H 2 O / mol SO 3 − to 15 mol H 2 O / mol SO 3 − when operated under fully humidified conditions, and only drier membranes exhibited membrane hydration during the low temperature operations. 4 The increase in HFR can be attributed to either a loss in electronic conductivity of the CL (due to ice formation moving the carbon particles further apart) or an increase in the interfacial (CL/MEA or MPL/CL) resistances.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with those reported earlier where the initial membrane water content, λ, was 14 mol H 2 O / mol SO 3 − to 15 mol H 2 O / mol SO 3 − when operated under fully humidified conditions, and only drier membranes exhibited membrane hydration during the low temperature operations. 4 The increase in HFR can be attributed to either a loss in electronic conductivity of the CL (due to ice formation moving the carbon particles further apart) or an increase in the interfacial (CL/MEA or MPL/CL) resistances.…”
Section: Resultsmentioning
confidence: 99%
“…Controlled isothermal experiments of single cells have been conducted to infer the location of ice formation and to study the performance of fuel cells at subfreezing temperatures. [3][4][5][6][7][8][9][10][11] These results have all shown that ice formation in the CL leads to a loss in cell performance, but there are few reported results on the durability of fuel cell stacks that have been subjected to subfreezing temperatures. Moreover, there is wide variability in the results reported, with Knights et al reporting no degradation after 55 subfreezing starts 12 and Yan et al demonstrating significant damage within a few subfreezing starts on a 25 cm 2 fuel cell.…”
mentioning
confidence: 99%
“…As discussed in the previous section, the maximum water content in previously predried membranes is similar whether the membrane is equilibrated in water vapor or liquid water [8,46,50,74]. In contrast to this, for membranes that are not predried (at elevated temperatures for a certain period of time), but subjected to standard treatment procedure, the water content is [10,38,45,46].…”
Section: Effect Of Initial (Residual) Water In the Membranementioning
confidence: 85%
“…However, it has been reported that [8,46,50] the water content in predried 3 membranes is similar, whether the membrane is equilibrated in saturated water vapor or liquid water. Thus, we will here adopt the results from a number of experimental water uptake studies for predried PFSA membranes equilibrated in liquid water and/or water vapor from Zawodzinski et al [8,38], Hinatsu et al [45], Onishi et al [46], and Thompson et al [74]. According to these studies, the water content of the predried membrane saturated with water is in the range of l ¼ 12-20, in close agreement with the predictions of our cylindrical RVE model (Fig.…”
Section: Effect Of Temperaturementioning
confidence: 99%
“…Tajiri et al proposed a strict gas purge process before cold start operation, and estimated the ice distribution in the cathode catalyst layer at the end of cold starting at -30 °C at low and high current densities [5]. Recently, cryo-SEM observations were conducted to elucidate further details of the ice distribution in the catalyst layer at -25 °C or -20 °C; these observations were carried out with the examined components kept at very low temperature and in vacuum conditions to avoid thawing and covering by frost deposits [6][7][8][9]. At temperatures closer to zero, like -10 °C, it was reported that the produced water is present in a supercooled state, and that the freezing behavior in a PEFC can be visualized by infrared thermography and it was possible to capture the 2-dimensional propagation in the high temperature region caused by the release of heat due to freezing [10][11][12].…”
Section: Introductionmentioning
confidence: 99%